The cyber-insurance market in Poland and determinants of its development from the insurance broker’s perspective - Strupczewski, Grzegorz (Economics and Business Review, 2017)
The aim of the paper is to analyze the state of the cyber-insurance market in Poland, and additionally the identification of key determinants of its development, including such issues as cyber-risk perception and the insurability of cyber-risk. Due to the lack of comprehensive, cross-industry insurance data on cyber-insurance, I decided to collect raw data through my own, computer-aided survey amongst insurance brokers operating in Poland. By conducting the survey amongst insurance brokers it was possible not only to collect data describing the state of Polish cyber-insurance market but also to use their expert opinion on various issues relating to cyber-risk. The research presented here is a pioneer in terms of analysis of a cyber-insurance market in a post-communist country such as Poland which is the most important emerging market in the CEE region as well. My paper makes the research perspective broader as most cyber-insurance industry reports have focused ing on the US, the UK or the developed countries of Western Europe.